Natural selection and convergent evolution of the HOX gene family in Carnivora - Fang, Wenxue; Li, Kexin; Ma, Shuai; Wei, Fuwen; Hu, Yibo (Frontiers in Ecology and Evolution, 2023)
HOX genes play a central role in the development and regulation of limb patterns. For mammals in the order Carnivora, limbs have evolved in different forms, and there are interesting cases of phenotypic convergence, such as the pseudothumb of the giant and red pandas, and the flippers or specialized limbs of the pinnipeds and sea otter. However, the molecular bases of limb development remain largely unclear. Here, we studied the molecular evolution of the HOX9 13 genes of 14 representative species in Carnivora and explored the molecular evolution of other HOX genes. We found that only one limb development gene, HOXC10, underwent convergent evolution between giant and red pandas and was thus an important candidate gene related to the development of pseudothumbs. No signals of amino acid convergence and natural selection were found in HOX9 13 genes between pinnipeds and sea otter, but there was evidence of positive selection and rapid evolution in four pinniped species. Overall, few HOX genes evolve via natural selection or convergent evolution, and these could be important candidate genes for further functional validation. Our findings provide insights into potential molecular mechanisms of the development of specialized pseudothumbs and flippers (or specialized limbs).